Penciptaan Patung Gerabah Bercitra Tokoh Hanoman sebagai Penguatan Nilai Budaya Lokal di Malang - Muhammad Hasyimy (Jurnal Pendidikan dan Penciptaan Seni, 2021)
Articles on pottery art creation originate from wayang plays, especially the Ramayana play. In Malang, East Java has started looking for an identity that reinforces the local cultural image. The image of local culture in Malang began to lead to the exploration of the source of the creation of wayang plays. Researchers since 2013 have begun to explore the possibility of creating pottery art, bearing in mind that research has also explored pottery centers in Pagelaran and Gelanggang. This center allows for integration, and even some creation research that has been carried out has also focused on the diversification of forms and functions. This is confirmed by the author's research using development methods, which include observation, planning, and manufacturing of ceramic products. The research design used qualitative data collected through interviews, observation and document review. The results show, 3 types of ceramic creation with Hanoman (Kera) character were formed as a development of pottery art creation techniques. The results of the pottery become the optimal medium for expressing the image of the characters from the Ramayana play, especially the Kumbakarna figures as a strengthening of local values in Malang, East Java.